More Than Just Hard Work: Educational Policies to Facilitate Economic Mobility. (October 2020) - Williams, Wendy R.; Reppond, Harmony A.
The COVID-19 pandemic exposed long-standing class-based inequities in education and as a result highlighted the role of structural supports (e.g., food, stable housing, income) promoting economic opportunity. Although social class mobility is often attributed to perceptions of hard work, science does not support these dominant narratives. Instead, access to quality education and structural supports correlate with economic uplift. By eliminating structural barriers to low-income college students' degree completion and coordinating efforts to assist low-income students, policymakers can restore the promise of economic mobility through education. This article focuses on the psychological and behavioral science that should inform higher education policy. As the country recovers from the COVID-19 pandemic, a structure-based, scientific approach to facilitate equal opportunity in higher education is vital to spurring greater economic mobility and avoiding further entrenchment of economic inequalities.